Stereoselective Knoevenagel reaction between pyrimidine carbaldehyde bearing an adjacent aryl group and active cyano-containing methylene compounds. (17th February 2023) - Yoshikawa, Takahiro; Hayashi, Naoto; Yamada, Akihiro; Yokota, Masayuki
Graphical abstract: Highlights: Knoevenagel reaction between pyrimidine carbaldehyde bearing an adjacent F-phenyl group and cyanoacetic acid were conducted. A product in which cyano and F-phenyl group were in a cis relationship was obtained stereoselectively. X-ray diffraction and MO calculations suggested that the CN/ π interaction was involved in this stereoselectivity. Abstract: The Knoevenagel reaction between cyanoacetic acid and 4-(4-fluorophenyl)-6-isopropyl-2-( N -methyl- N -methanesulfonylamino)-5-pyrimidinecarboxaldehyde (1 ), which contains an aryl group adjacent to the formyl group in the pyrimidine-5-carbaldehyde moiety, was found to proceed stereoselectively to give an alkene product bearing cyano and phenyl groups in a cis relationship. Similar selective reactions also occurred between 1 and several active methylene compounds bearing a cyano group. An X-ray structure analysis of the alkene products and molecular orbital calculations suggested that the attractive CN/ π interaction between the cyano and 4-fluorophenyl groups of 1 plays an important role in the selectivity by stabilizing the carbocation intermediates.